Analisis Demokrasi pada Era Desentralisasi dalam Perspektif Administrasi Publik - Azfirmawarman, Dony; Naldi, Hendra; Frinaldi, Aldri; Magriasti, Lince (Faculty of Social and Political Science, 2024)
This study explores the integration of democratic principles into decentralization policies in Indonesia and their impact on local governance. Indonesia's decentralization journey began with Law No. 22 of 1999 and evolved through subsequent legal reforms, including Law No. 32 of 2004 and Law No. 23 of 2014. These reforms aimed to enhance local government autonomy, foster community engagement, and promote accountability in addressing local needs. Employing qualitative methods, the study analyzes public administration theories, leadership frameworks, and organizational dynamics to evaluate the effectiveness of decentralization efforts. Findings highlight decentralization’s role in empowering local governments and increasing public participation in policymaking. However, challenges such as inadequate administrative capacity, fiscal disparities, and corruption hinder optimal outcomes. The paper concludes by offering strategic recommendations to bolster decentralization, enhance democratic governance, and ensure equitable development. By bridging theoretical insights with practical implications, this research contributes to a nuanced understanding of the successes and limitations of decentralization in strengthening local democracy in Indonesia.